Cover Feature: Triplet‐triplet Annihilation Dynamics of Naphthalene (Chem. Eur. J. 40/2022). Issue 40 (27th June 2022) - Gudem, Mahesh; Kowalewski, Markus
Abstract : Triplet–triplet annihilation (TTA)‐based photon upconversion involves the fusion of two non‐emissive triplet excited states into one singlet excited state. The TTA process in naphthalene is found to be mediated by conical intersection between the T1 T1 and S1 S0 states. The coupling of an optical cavity to a naphthalene dimer results in an increase in the efficiency of TTA‐assisted photon upconversion process. More information can be found in the Research Article by M. Gudem and M. Kowalewski (DOI: 10.1002/chem.202200781 ).